2021
DOI: 10.1021/acs.bioconjchem.0c00621
|View full text |Cite
|
Sign up to set email alerts
|

Taking Advantage of the Morpheein Behavior of Peroxiredoxin in Bionanotechnology

Abstract: Morpheeins are proteins that reversibly assemble into different oligomers, whose architectures are governed by conformational changes of the subunits. This property could be utilized in bionanotechnology where the building of nanometric and new high-ordered structures is required. By capitalizing on the adaptability of morpheeins to create patterned structures and exploiting their inborn affinity toward inorganic and living matter, “bottom-up” creation of nanostructures could be achieved using a single protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 142 publications
(430 reference statements)
0
6
0
Order By: Relevance
“…In the case of the regulation of the human transcription factor STAT3, which is oxidized by HsPRX2, the interaction is stabilized by the presence of ANNEXIN A2 ( Talwar et al., 2020 ). Furthermore, HsPRX3 forms stacks and tubes depending on pH and redox state ( Ardini et al., 2021 ). Reduced HMW aggregates of HsPRX3, as shown here, may serve as storage pools to release dimers and decamers for efficient peroxide detoxification controlling apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the regulation of the human transcription factor STAT3, which is oxidized by HsPRX2, the interaction is stabilized by the presence of ANNEXIN A2 ( Talwar et al., 2020 ). Furthermore, HsPRX3 forms stacks and tubes depending on pH and redox state ( Ardini et al., 2021 ). Reduced HMW aggregates of HsPRX3, as shown here, may serve as storage pools to release dimers and decamers for efficient peroxide detoxification controlling apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Their monomers are nucleotides and amino acids, respectively, while viruses are larger particles, essentially comprised of a capsid made of proteins that surrounds a molecule of nucleic acid ( Stephanopoulos, 2020 ). These biomolecules are characterized by high structural complexity, specific binding capability, catalytic activity and in some cases high stability in extreme conditions on temperature pressure and pH ( Stephanopoulos, 2020 ; Ardini et al, 2021 ). DNA (deoxyribonucleic acid) is a polymer of nucleotides forming a double-helix of antiparallel strands.…”
Section: Graphene-based Materialsmentioning
confidence: 99%
“…They showed that this protein can self-assemble with GO sheets dispersed in an aqueous solution at neutral pH, interacting via weak intermolecular interactions. Moreover, due to the presence of cysteine residues, Sm PrxI is also able to simultaneously reduce GO ( Ardini et al, 2016 ; Ardini et al, 2021 ). Furthermore, due to the presence of several His-tags exposed in its lumen, Sm PrxI can bind gold nanoparticles functionalized with nitrilotriacetic acid (NTA) in presence of nickel, or even promote the in situ growth of palladium nanoparticles.…”
Section: Graphene-based Materialsmentioning
confidence: 99%
“…Biomolecules represent naturally occurring ready-to-use nanomaterials as they are nanoscopic objects with regular shape, high binding specificity and affinity, surfaces suitable for chemical functionalization and catalytic activity as in the case of enzymes, for instance [ 4 ]. Moreover, biomolecules can be modelled via genetic and protein engineering [ 5 , 6 ] and their surfaces enable the interaction with other nanomaterials; as a result, biomolecules have been widely exploited to functionalize nanomaterials thus enabling precise tailoring of hybrid functional bioconjugates at the nanoscale [ 7 , 8 , 9 ]. Beyond biomolecules, organic and inorganic nanomaterials with sharpen architecture have attracted interest for their high surface-to-volume ratio, conductivity, shock-bearing ability and optical tunability, e.g., nanoparticles, nanotubes, nanorods, graphene, nanofibers, molybdenum disulfide, carbides, nitrides, carbonitrides and quantum dots [ 3 ].…”
Section: Introductionmentioning
confidence: 99%